Does pronator quadratus repair affect functional outcome following volar plate fixation of distal radius fractures? A systematic review and meta-analysis - Ying, Liwei; Cai, Guoping; Zhu, Zhong; Yu, Guoliang; Su, Yongwei; Luo, Hua (Frontiers in Medicine, 2023)
The study aimed to evaluate the efficacy of pronator quadratus (PQ) repair versus no repair following volar plate fixation of distal radius fractures. A comprehensive search was performed in PubMed, CNKI, EMBASE, Web of Science, Ovid, and Cochrane Library databases. All randomized controlled trials comparing PQ repair with no repair in distal radius fractures before March 2022 were included. Two investigators independently screened eligible articles, assessed the study quality, and extracted data from included studies. The meta-analysis was performed using the Revman 5.4 software. A total of 430 patients in 7 RCT studies were included, of which 218 underwent pronator quadratus repair, while 212 patients underwent no repair. The results of the meta-analysis displayed statistically significant differences in the grip strength during 3-month follow-up, pronation angle during 3-month follow-up, and pronation strength during 3- and 12-month follow-up between the two treatments. No significant difference in other outcomes was found between the two treatment arms. The repair of pronator quadratus may further increase grip strength and pronation function in the short-term, as well as enhance long-term pronator muscle strength compare to no repair. However, due to the small number of articles included in the article, the above conclusions need to be verified by a larger sample and multi-center clinical study.